Artificial Intelligence in Criminal Justice: Predictive Tools, Evidentiary Challenges, and Human Rights Implications - Koshevaliska, Olga (NBP. Nauka, bezbednosti, policija, 2026)
Integrating artificial intelligence (AI) technologies into criminal justice systems introduces both transformative opportunities and profound legal dilemmas. This paper critically examines the use of AI in crime prediction, risk assessment, evidence analysis, and sentencing, with particular attention to its impact on fundamental procedural rights. Focusing on predictive policing algorithms, facial recognition systems, and AI-assisted evidence review, the research explores how these tools reshape police, prosecutorial, and judicial discretion. Key challenges include transparency, explainability, and risks of systemic bias or “automated justice,” contrasted with constitutional guarantees such as the presumption of innocence, the right to a fair trial, and the principle of legality. The study concludes that while AI can enhance efficiency and accuracy, its uncritical adoption may jeopardize essential human rights protections unless accompanied by robust procedural safeguards. Artificial intelligence should serve as an instrument of human progress, not as a substitute for human judgment.
Keywords: AI in criminal law, algorithmic evidence, risk assessment tools, predictive policing, fair trial, legal safeguards, procedural rights.